The astructural bias charge myth or reality? - Musolf, Gil Richard, 1951- (Bingley, U.K. : Emerald, 2016)
The charge that symbolic interactionism (SI) is impaired by an astructural bias orbits around a number of sociology's core concerns: structure and agency, methodological individualism and methodological holism, the micro-macro link, the proper procedures to conduct research and when to state and how to test hypotheses and, whether interactionism can address structural concerns such as class, race, gender, power, and oppression. The Astructural Bias: Myth or Reality constitutes a collection of outstanding essays by scholars who address the concern of an astructural bias. Chapters explore the nature of social structure and SI's effectiveness in using the concept. This volume is beneficial for contemporary interactionists and their critics, social theorists, and all students of sociology who are interested in assessing the ability of SI to fully address the grave social circumstances and social problems of an increasingly precarious and dangerous world.
Ruinous reification: the astructural bias in symbolic interactionism / Patrick McGinty -- The intellectual origins of the debate over the astructural bias / Gil Musolf -- Jane Addams, the Chicago schools of sociology, and the emergence of symbolic interaction, 1889-1935 / Mary Deegan -- Mead's field theory and its implications for American minorities / Norbert Wiley -- Overcoming aprocessual bias in the study of inequality: parsing the capitalist interaction order / Michael Schwalbe -- Symbolic interaction and narrative productions of meaning in public spaces / Donileen Loseke -- The persistence of the power deficit? Advancing power premises in contemporary interactionist theory / Natalia Ruiz-Junco -- Astructure/which structure?: Rethinking'astructural bias' in symbolic interaction through Georges Bataille and his followers / Steve Bailey -- Final assessments / Gil Musolf -- Alcoholism and the Simpsons: connecting symbolic interactionism and pastiche / Michael Katovich, Sarah Rosenthal Vaughan.
Includes bibliographical references.
Print version record
Keywords: Social Science, Social Classes; Social interaction; Symbolic interactionism